The Role of Social Support Networks in Enhancing the Well-being of Elderly People (Teacher Half-Yearly Journal, 2025)
This paper explores the relationships between age, social support, marital status, subjective well-being, and perceptions of general health among elderly people. The data were collected using the convenience sampling, and a survey was conducted among 138 respondents, predominantly women 78.3 percent, with 40 percent single and 56.9 percent aged between 61- 91 years. Correlation analysis showed significant relationships between age and overall perceived health (r=0.23), self-esteem (r=0.19), and life satisfaction (r=0.22). Furthermore, there was a favorable correlation (r=0.19) between self-esteem, social support, and well-being. The elderly reported higher amounts of social support, particularly emotional (r=0.26) and private (r=0.19). A mean well being rating for the elderly was 67.03 and indication of good attitude. Social support was found to have only an indirect effect, mainly decreased with age while life happiness and age were identified as the most significant predictors of how people felt about their overall health. The results indicated that age and other aspects of well-being, including self-perceived health, self-esteem, and life satisfaction were moderate and associated with those of older female respondents. It was also confirmed by the results that there was a positive correlation between the social support and wellbeing.